Development and preliminary numerical investigations of a dislocation density-based finite-strain rate-dependent elastoplasticity constitutive model - Garschagen, Emma (Department of Mechanical Engineering, 2025)
Development and preliminary numerical investigations of a dislocation density-based finite-strain rate-dependent elastoplasticity constitutive model Finite-strain elastoplasticity constitutive models suitable for process-scale simulation are typically developed from empirical observations of phenomena of interest. Such models make use of internal state variables that do not directly represent the associated evolution of the material microstructure, such as accumulated plastic strain. As a result, these models cannot directly provide microstructural information that may be of interest. In an attempt to bridge this gap, a mechanistically-motivated, multiaxial, finite-strain, rate-dependent elastoplasticity constitutive model in which average dislocation density is used as an internal state variable is developed in this work. The relationship between dislocation-based phenomena and working hardening in face-centred cubic metals is well-researched, and the popular Kocks-Mecking model for average dislocation density evolution has been successfully implemented in small-strain elastoplasticity constitutive models. However, in contrast to other dislocation-based rate-dependent elastoplasticity models, the model presented in this work is formulated in a multiaxial, finite-strain framework that is suitable for the macro-scale simulation of wrought metal production processes. Work hardening as a result of large deformation is modelled as a function of average dislocation density, which is described by the Kocks-Mecking and finite-strain Hariharan-Barlat models. The behaviour of the model is elucidated after a material point-level numerical implementation and computational experiments with several test cases, such as plane strain compression, uniaxial compression, and cyclical loading. The model is fit to 5XXX series aluminium mechanical test data sourced from literature, and from preliminary investigations, it is shown that the work hardening behaviour and associated dislocation density evolution under the given loading conditions concurs with general trends seen in literature.